SNARE proteins are highly enriched in lipid rafts in PC12 cells: Implications for the spatial control of exocytosis - Chamberlain, Luke H. (The National Academy of Sciences, 2001)
Lipid rafts are microdomains present within membranes of most cell types. These membrane microdomains, which are enriched in cholesterol and glycosphingolipids, have been implicated in the regulation of certain signal transduction and membrane traffic pathways. To investigate the possibility that lipid rafts organize exocytotic pathways in neuroendocrine cells, we examined the association of proteins of the exocytotic machinery with rafts purified from PC12 cells. The target soluble N-ethylmaleimide-sensitive factor attachment protein receptor (tSNARE) proteins syntaxin 1A and synaptosomal-associated protein of 25 kDa (SNAP-25) were both found to be highly enriched in lipid rafts (≈25-fold). The vesicle SNARE vesicle-associated membrane protein (VAMP)2 was also present in raft fractions, but the extent of this recovery was variable. However, further analysis revealed that the majority of VAMP2 was associated with a distinct class of raft with different detergent solubility characteristics to the rafts containing syntaxin 1A and SNAP-25. Interestingly, no other studied secretory proteins were significantly associated with lipid rafts, including SNARE effector proteins such as nSec1. Chemical crosslinking experiments showed that syntaxin1A/SNAP-25 heterodimers were equally present in raft and nonraft fractions, whereas syntaxin1A/nSec1 complexes were detected only in nonraft fractions. SDS-resistance assays revealed that raft-associated syntaxin1A/SNAP-25 heterodimers were able to interact with VAMP2. Finally, reduction of cellular cholesterol levels decreased the extent of regulated exocytosis of dopamine from PC12 cells. The results described suggest that the interaction of SNARE proteins with lipid rafts is important for exocytosis and may allow structural and spatial organization of the secretory machinery.